2015
DOI: 10.1002/pbc.25678
|View full text |Cite
|
Sign up to set email alerts
|

An Increased Risk of Second Malignant Neoplasms After Rhabdomyosarcoma: Population‐Based Evidence for a Cancer Predisposition Syndrome?

Abstract: Background Rhabdomyosarcoma survivors have an increased risk of developing second malignant neoplasms (SMN); this risk is traditionally attributed to the effects of multidisciplinary management required for cure. However, the impact of constitutional predisposition has not been properly analyzed. Methods We analyzed the risk of SMN among 1,151 children diagnosed with rhabdomyosarcoma and reported to the Surveillance, Epidemiology, and End Results registries (SEER‐9) from 1973 to 2010. Standardized incidence ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
35
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 14 publications
5
35
2
Order By: Relevance
“…The greatest relative risk of second primary cancers in our study was for people diagnosed with rhabdomyosarcoma during childhood; the SIR of 19.9 was much higher than the 5.7 estimated by a United States study that included people diagnosed with rhabdomyosarcomas before the age of 19 years during 1973-2010. 19 However, the authors of the American study noted that most of the second cancers identified were in people with first primary rhabdomyosarcoma diagnoses during 2000-2010; restricting analysis to these cases resulted in a SIR of 21, similar to our figure. Without explaining the recent sharp rise in relative risk for people diagnosed with childhood rhabdomyosarcoma, the authors suggested that they may be genetically predisposed to cancer, adding to the effects of exposure to chemotherapy and radiotherapy while young.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…The greatest relative risk of second primary cancers in our study was for people diagnosed with rhabdomyosarcoma during childhood; the SIR of 19.9 was much higher than the 5.7 estimated by a United States study that included people diagnosed with rhabdomyosarcomas before the age of 19 years during 1973-2010. 19 However, the authors of the American study noted that most of the second cancers identified were in people with first primary rhabdomyosarcoma diagnoses during 2000-2010; restricting analysis to these cases resulted in a SIR of 21, similar to our figure. Without explaining the recent sharp rise in relative risk for people diagnosed with childhood rhabdomyosarcoma, the authors suggested that they may be genetically predisposed to cancer, adding to the effects of exposure to chemotherapy and radiotherapy while young.…”
Section: Discussionsupporting
confidence: 80%
“…Without explaining the recent sharp rise in relative risk for people diagnosed with childhood rhabdomyosarcoma, the authors suggested that they may be genetically predisposed to cancer, adding to the effects of exposure to chemotherapy and radiotherapy while young. 19 Endocrine system-related second primary cancers were relatively frequent among 5-year survivors in our study, particularly thyroid and breast cancers. Radiotherapy is the only risk factor for subsequent development of these two solid cancer types supported by strong clinical evidence.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Patient 1 did not harbor a germline mutation in a tumor suppressor gene, but epidemiologic data suggest that children diagnosed with rhabdomyosarcoma (embryonal and pleomorphic subtypes) have heightened risk of developing SMNs (50). Clearly the molecular basis for SMN risk remains to be defined for many pediatric cancer survivors.…”
Section: Discussionmentioning
confidence: 99%
“…4 Nevertheless, published reports have suggested that Ewing sarcomas (F 1 sarcomas) are not represented among the spectrum of sarcomas diagnosed in TP53 mutation carriers. 5 In addition, our recently published work indicates that individuals with alveolar rhabdomyosarcoma (mostly F 1 soft-tissue sarcomas) are less likely to have a first-degree relative with cancer 6 or to develop a second malignancy 7,8 compared with those with embryonal or pleomorphic rhabdomyosarcoma (F-soft tissue sarcomas).…”
Section: Introductionmentioning
confidence: 99%